Perlindungan Hukum Terhadap Hak Cipta Karya Tulis Dalam Media Internet - Bayu Rizki Ramadhan; Nahrowi Nahrowi (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to explain how the protection of writings on the internet that are widely circulated and the rise of violations that occur in the internet media. Especially violation of piracy or plagiarism of papers in the internet media, in the provisions of Law Number 28 of 2014 concerning Copyright, Article 1 Paragraph (1) states that copyright is an exclusive right in which the protection is automatically granted by the law since the creation is realized in real form. This protection limited to creations in physical form but includes all creations in physical or non-physical forms such as online media. This research method uses a normative approach. The data collection technique used is the study of literature, namely research conducted by finding references to support this research material through various literature such as books, lecture materials, articles, journals, theses, laws and document results. The results of research conducted by a researcher are that legal protection on the internet is normatively well regulated by Law Number 28 of 2014 concerning Copyright, as well as legal sanctions imposed on violators of the provisions of reasonable limits in taking or quoting written works have not been regulated in the provisions of the Copyright Act.Keywords: Protection Law, Papers, Copyright, Internet